Temperature-Induced Errors in ITTC Model-Ship Extrapolation - Sang-seok Han; Saishuai Dai; Momchil Terziev; Daejeong Kim; Tahsin Tezdogan; Doojin Jung; Soonseok Song (Journal of Marine Science and Engineering, 2025)
This study addresses the question: “Does the towing tank water temperature affect the result of model-ship extrapolation?” While it is well-established that temperature variations affect Reynolds numbers and consequently frictional and viscous resistance, this study examines whether the ITTC 1978 extrapolation method properly compensates for these effects. Although current procedures consider temperature indirectly through the Reynolds number, they assume that the form factor depends solely on the Froude number and is insensitive to viscosity changes. Our analysis reveals that the form factor is also temperature-sensitive, indicating a fundamental limitation in the conventional approach. This sensitivity arises from the limitations of the ITTC 1957 friction curve and the method’s neglect of temperature-induced variations in the form factor. To quantify the effect of temperature, model-scale CFD simulations were conducted for two ship models (KCS and KVLCC2) at different water temperatures using the ITTC 1978 procedure with Prohaska’s method. The results show that the ship-scale total resistance coefficient (CT) can vary by up to 2.8% depending on the water temperature and friction line selection. This demonstrates that the ITTC 1978 performance prediction method fails to adequately compensate for the temperature-induced changes in resistance, which leads to systematic errors in the extrapolated results.